Histidine–dialkoxyanthracene dyad for selective and sensitive detection of mercury ions. Issue 4 (3rd April 2018) - Patil, Sachin; Belhajjame, Widad; Moosa, Basem; Khashab, Niveen M.
Abstract: Histidine-dialkoxyanthracene (HDA) was synthesised as a turn off type fluorescent sensor for fast and sensitive detection of mercury ions (Hg 2+ ) in aqueous media. The two histidine moieties act as 'claws' to selectively complex Hg 2+ . The binding ratio of HDA to Hg 2+ was 1:1 (metal-to-ligand ratio). The association constant for Hg 2+ towards the receptor HDA obtained from Benesi–Hildebrand plot was found to be 3.22 × 10 4  M −1 with detection limit as low as 4.7 nM (0.94 μg/L). Abstract :